The new politics of the handmade craft, art and design - Black, Anthea; Burisch, Nicole 1980- (Bloomsbury Visual Arts, 2021)
"The handmade has become inseparable from capitalist modes of production and consumption and this change demands new understandings of objects, aesthetics and labour. Drawing on a wide range of case studies of craft practice, Craft on Demand examines the role of the handmade in contemporary art, craft and design as part of a dramatically shifting global economy. New writing and artists' projects by international scholars and practitioners explore the politics of scarcity, hoarding and sustainability, craftivism and 'ethical' consumption, urban space and new technologies, race, cultural heritage and sovereignty. Engaging with craft, art, design students and practitioners who want a radical rethink of the politics and economics of the handmade, they claim craft as a dynamic critical field for thinking through the most immediate issues of our time"--Provided by publisher.